Brief Report: Blockade of Notch Signaling in Muscle Stem Cells Causes Muscular Dystrophic Phenotype and Impaired Muscle Regeneration123. (20th March 2013) - Lin, Shuibin; Shen, Huangxuan; Jin, Baofeng; Gu, Yumei; Chen, Zirong; Cao, Chunxia; Hu, Chengbin; Keller, Charles; Pear, Warren S.; Wu, Lizi
Abstract Muscular dystrophies are a group of devastating diseases characterized by progressive muscle weakness and degeneration, with etiologies including muscle gene mutations and regenerative defects of muscle stem cells. Notch signaling is critical for skeletal myogenesis and has important roles in maintaining the muscle stem cell pool and preventing premature muscle differentiation. To investigate the functional impact of Notch signaling blockade in muscle stem cells, we developed a conditional knock‐in mouse model in which endogenous Notch signaling is specifically blocked in muscle stem cell compartment. Mice with Notch signaling inhibition in muscle stem cells showed several muscular dystrophic features and impaired muscle regeneration. Analyses of satellite cells and isolated primary myoblasts revealed that Notch signaling blockade in muscle stem cells caused reduced activation and proliferation of satellite cells but enhanced differentiation of myoblasts. Our data thus indicate that Notch signaling controls processes that are critical to regeneration in muscular dystrophy, suggesting that Notch inhibitor therapies could have potential side effects on muscle functions. STEM CELLS2013;31:823–828